De l'équipe vers un collectif de travail en institut de formation : le rôle d'une image opérative partagée - Thierry Piot (Université de Provence, 2014)
This article focuses on the requirements concerning the construction of a collective subject within a team of training facilitators and focuses on the central role of the development of a shared operative image (Ochanine) .On the theoretical level, it relies on current vocational teaching methods which permit an analysis of the actual working situations of training facilitators to be made. A survey was conducted among trainers belonging to an educational nursing institute, focusing on the mission of student follow-up throughout the three years of their vocational training. The results indicate that the construction of a shared operative image that goes beyond an individual operative image is a decisive factor for the emergence of a collective subject within the training team. They also point out the critical role of coordination between trainers, often driven by the management imperatives of their training institute.